Orientalism in the Cinématographe: The Visualization of Eastern-Exoticism in Alexandre Promio’s Recorded Films in Egypt 1897 - Tizani, Fahmi (Socio Historica: Journal of Islamic Social History, 2025)
This study discusses the representation of Eastern-Islamic exoticism in Egypt’s earliest films recorded by Alexandre Promio, an operator for the Société Antoine Lumière et ses Fils (Société Lumière) owned by the Lumière Brothers, using the late 19th-century European invention, the Cinématographe Lumière. The primary objective of this research is to examine the cultural transformation of Western-European (French) visual representation and how Alexandre Promio represented Eastern-Islamic (Egyptian) exoticism through the first moving pictures (films) about Egypt, to establish or reinforce ideological stereotypes held by Western Europeans. The primary sources used in this study include 21 of the 35 Egypt’s earliest films made by Alexandre Promio, along with contemporary photographs, lithographs, paintings, books, magazines, and newspapers. This study utilizes the historical research method with a constructionist approach. The research findings indicate that Promio did not merely record reality, but through the selection of subjects, framing, and scene duration, he systematically visualized exoticism centered on monumental landscapes, bustling markets, and religious objects. This confirms Promio's effort to construct new visual stereotypes and reinforce Western-European (French) ideological understanding of Egypt as The Other that is exotic, static, yet visually stunning. These films served as a visual blueprint that subsequently influenced stereotypes in later colonial cinema, making them an important vehicle for reinforcing Western ideological understanding of the Orient.